The professional autonomy of nursing in pandemic times - Rafaela Lira Mendes Costa; Regina Maria dos Santos; Laís de Miranda Crispim Costa (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective To reflect on the exercise of Nursing's professional autonomy in times of pandemic. Method Theoretical reflection in the light of the Sociology of Professions proposed by Eliot Freidson. Using the author's main concepts, it was sought to understand the professional practice of Nursing in times when its protagonism in the care process becomes even more challenging. Results Although there are obstacles in the daily work, it is believed that an autonomous practice contributes satisfactorily to the performance of nurses, since by revealing all the potential and leadership they have, they allow their professional autonomy to be legitimized. Final Considerations The reflection clarified the importance of nurses to put their professional autonomy into practice, in order to achieve greater recognition and social appreciation of their work in times of pandemic.